2020
DOI: 10.1126/science.aba1948
|View full text |Cite
|
Sign up to set email alerts
|

Earth’s water may have been inherited from material similar to enstatite chondrite meteorites

Abstract: The origin of Earth’s water remains unknown. Enstatite chondrite (EC) meteorites have similar isotopic composition to terrestrial rocks and thus may be representative of the material that formed Earth. ECs are presumed to be devoid of water because they formed in the inner Solar System. Earth’s water is therefore generally attributed to the late addition of a small fraction of hydrated materials, such as carbonaceous chondrite meteorites, which originated in the outer Solar System where water was more abundant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
140
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 228 publications
(158 citation statements)
references
References 60 publications
16
140
1
1
Order By: Relevance
“…70, 80, and 81) is questionable. Recently, Piani et al (82) suggested that about three oceans of H 2 O could have been delivered by material similar to enstatite chondrites throughout its accretion, but this does not account for loss of H 2 O during planetesimal or embryo differentiation, and so is likely an overestimate.…”
Section: Of 8 | Pnasmentioning
confidence: 99%
“…70, 80, and 81) is questionable. Recently, Piani et al (82) suggested that about three oceans of H 2 O could have been delivered by material similar to enstatite chondrites throughout its accretion, but this does not account for loss of H 2 O during planetesimal or embryo differentiation, and so is likely an overestimate.…”
Section: Of 8 | Pnasmentioning
confidence: 99%
“…
Understanding the origin of life-essential volatiles like nitrogen (N) in the SolarSystem and beyond is critical to evaluate the potential habitability of rocky planets [1][2][3][4][5] .Whether the inner Solar System planets accreted these volatiles from their inception or had an exogenous delivery from the outer Solar System is, however, not well understood. Using previously published data of nucleosynthetic anomalies of Ni, Mo, W and Ru in iron meteorites along with their 15 N/ 14 N ratios, here we show that the earliest formed protoplanets in the inner and outer protoplanetary disk accreted isotopically distinct N.While the Sun and Jupiter captured N from nebular gas 6 , concomitantly growing protoplanets in the inner and outer disk possibly sourced their N from organics and/or dust with each reservoir having a different N isotopic composition.
…”
mentioning
confidence: 99%
“…Rock magnetism methods are cost effective, weakly destructive and do not necessitate important amounts of material. They could also be appropriate to investigate extraterrestrial spinel‐bearing rock samples, allowing to track fluid/rock interaction in primitive meteorites and thus possibly providing important clues about the origin of water on Earth (e.g., Piani et al., 2020).…”
Section: Discussionmentioning
confidence: 99%